Caracterização das propriedades neuromorfológicas e proliferativas do telencéfalo do lagarto Tropidurus hispidus - Pimentel, Hugo de Carvalho (2014)
For the last twenty years, a large number of data has been provided in favor of the hypothesis of new neurons being generated throughout the entire lifespan of some groups of animals. This phenomenon is known as postnatal neurogenesis. However, the physiological relevance of the increase in the neuronal population of some brain areas is not yet clear. In this sense, reptiles seem to be useful models for the study of postnatal neurogenesis and neuronal regeneration. The tropical lizards Tropidurus hispidus were shown to be examples of that, since they form new neurons throughout their entire lifespan. However, data on neuroanatomy and neurogenesis of this species have not yet been fully provided. Therefore, the aims of this study were to characterize the neuroanatomy and neuromorphology, to study the distribution of zinc terminal areas, to verify the neuronal proliferation pattern of these lizards when under different temperatures and to describe proliferative areas and neuronal migration pathways of the T. hispidus telencephalon. We used the Nissl technique to characterize anatomy; Golgi impregnations to characterize neuronal morphology; Neo-Timm histochemistry to detect zinc terminals; Doublecortin (DCX) immunohistochemistry as a marker of neuronal proliferation; NeuN immunohistochemistry to detect mature neurons; Glial fibrillary acidic protein (GFAP) to detect glia; and 5-bromodioxiuridine (BrDU) to detect cellular divisions. Our results show that T. hispidus lizards have at least ten different neuronal types in their cortical areas: granular (uni-, bi- and multipolar), pyramidal (normal, inverted, open, bipyramidal and horizontal), spherical horizontal and fusiform. Furthermore, we verified that the zinc-positive regions were in cortical areas, septum, striatum and amygdaloid complex. BrDU immunohistochemistry showed that in lizards maintained in warm temperatures (28oC), new cells were evenly distributed in the ventricle walls and in the nervous parenchyma. In cold temperatures (16oC), new cells concentrated near ventricle walls. The number of new cells, however, was not different between groups. This suggested that temperature changes may impair migration but not formation of new cells. DCX immunohistochemistry showed that there are four main neurogenic foci in T. hispidus: lateral, septomedial, ventral and terminal sulci. We further observed the existence of four patterns of neuronal migration: radial, rostraltangential (similar to the mammalian rostral migratory stream), caudal-tangential and commissural. Therefore, these data seem to support the hypothesis that the Tropiduridae family is important to understanding mechanisms of postnatal neurogenesis, and is useful to future studies on comparative neurobiology.